Hospital volume and adverse events following esophageal endoscopic submucosal dissection in Japan - Odagiri, Hiroyuki; Yasunaga, Hideo; Matsui, Hiroki; Matsui, Shigeru; Fushimi, Kiyohide; Kaise, Mitsuru (Endoscopy, 2017)
Background and study aims Esophageal endoscopic submucosal dissection (ESD) has gradually acquired popularity as a minimally invasive surgery for early cancers not only in Japan, but also in other countries. However, most reported outcomes have been based on relatively small samples of patients from specialized centers. Therefore, the association between hospital volume and the rate of adverse events following esophageal ESD has been poorly understood.Patients and methods Using a nationwide administrative database in Japan, we identified patients who underwent esophageal ESD between 1 July 2007 and 31 March 2013. Hospital volume was defined as the number of esophageal ESD procedures performed per year at each hospital and was categorized into quartiles.Results In total, 12 899 esophageal ESD procedures at 699 institutions were identified during the study period. Perforation and perforation-related disorders were observed in 422 patients (3.3 %), and one patient died after perforation. There was a significant association between a lower hospital volume and a higher proportion of adverse events following esophageal ESD. Although not statistically significant, a similar tendency was observed in the occurrence of blood transfusion within 1 week after ESD and all-cause in-hospital death. Multivariable logistic regression analysis showed that hospitals with very high case volumes were less likely to experience adverse events following esophageal ESD than hospitals with very low volumes.Conclusions The proportion of perforation and perforation-related disorders following esophageal ESD was permissibly low, and there was a linear association between higher hospital volume and lower rates of adverse events following esophageal ESD.